2015
DOI: 10.3174/ajnr.a4559
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Leakage Patterns from Dynamic Susceptibility Contrast Perfusion MRI in the Grading of Primary Pediatric Brain Tumors

Abstract: BACKGROUND AND PURPOSE:The pattern of contrast leakage from DSC tissue signal intensity time curves have shown utility in distinguishing adult brain neoplasms, but has limited description in the literature for pediatric brain tumors. The purpose of this study is to evaluate the utility of grading pediatric brain tumors with this technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 25 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…While DSC and arterial spin-labeling perfusion metrics have been reported for pediatric brain tumor grading, [21][22][23] there are fewer studies using DCE-MR imaging. 6 Our results show that among the DCE-MR imaging parameters, K trans , K ep , and v e all successfully distinguished low-and high-grade tumors, and this result is consistent with our report from a smaller cohort.…”
Section: Discussionmentioning
confidence: 99%
“…While DSC and arterial spin-labeling perfusion metrics have been reported for pediatric brain tumor grading, [21][22][23] there are fewer studies using DCE-MR imaging. 6 Our results show that among the DCE-MR imaging parameters, K trans , K ep , and v e all successfully distinguished low-and high-grade tumors, and this result is consistent with our report from a smaller cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to restricted diffusion (ADC ~0.6 3 10 −3 mm 2 /sec), dynamic susceptibility contrast (DSC) perfusion imaging of AT/RTs shows a "return to baseline" pattern, without a T1-or T2*-dominant contrast material leakage pattern. Spectroscopy shows an aggressive metabolite pattern, with elevated choline, lipid, and lactate peaks (69)(70)(71).…”
Section: Atypical Teratoid/rhabdoid Tumormentioning
confidence: 99%
“…5) requires appropriate correction, such as small preload dose (0.025–0.05 mmoL/kg) of a gadolinium contrast agent or posthoc leakage-correction algorithms, to obtain correct perfusion values from DSC imaging (727). Ho et al (33) reported that time-intensity curves of DSC imaging could be categorized into T1-dominant leakage pattern (n = 25), T2 * -dominant leakage pattern (n = 15), and return to baseline (n = 23; ± 10% range) in 63 pediatric brain tumors. They also reported that T1-dominant leakage pattern was highly specific for a low-grade tumor, such as pilocytic or pilomyxoid astrocytoma.…”
Section: Perfusion Imagingmentioning
confidence: 99%